Risk/benefit tradeoff of habitual physical activity and air pollution on chronic pulmonary obstructive disease: findings from a large prospective cohort study - Chen, Lan; Cai, Miao; Li, Haitao; Wang, Xiaojie; Tian, Fei; Wu, Yinglin; Zhang, Zilong; Lin, Hualiang (BMC medicine, 2022)
The combined health impact of physical activity (PA) and air pollution on chronic obstructive pulmonary disease (COPD) remains unclear. We investigated the joint effects of habitual PA and long-term fine particulate matter (PM ) exposure on COPD incidence in a prospective population-based cohort. A prospective cohort study was conducted using data from the UK Biobank. Incidence of COPD was ascertained through linkage to the UK National Health Services register. Annual mean PM concentration was obtained using land use regression model. PA was measured by questionnaire and wrist-worn accelerometer. Cox proportional hazard models were applied to examine the associations between PM , PA, and COPD. Additive and multiplicative interactions were examined. A total of 266,280 participants free of COPD at baseline were included in data analysis with an average follow-up of 10.64 years, contributing to around 2.8 million person-years. Compared with participants with low level of PA, those with higher PA levels had lower risks of COPD incidence [hazard ratio (HR): 0.769, 95% CI: 0.720, 0.820 for moderate level; HR: 0.726, 95% CI: 0.679, 0.776 for high level]. By contrast, PM was associated with increased risk of COPD (HR per interquartile range increment: 1.065, 95% CI: 1.032, 1.099). Limited evidence of interaction between habitual PA and PM exposure was found. Similar results were found for accelerometer-measured PA. Our study suggests that habitual PA could reduce risk of COPD incidence, and such protective effects were not affected by ambient PM pollution exposure.